1929 : inside the greatest crash in Wall Street history--and how it shattered a nation [compact disc, unabridged] - Sorkin, Andrew Ross (Penguin Random House, 2025)
"From the bestselling author of Too big to fail, "the definitive history of the 2008 banking crisis," comes a spellbinding narrative of the most infamous stock market crash in history. With the depth of a classic history and the drama of a thriller, 1929 unravels the greed, blind optimism, and human folly that led to an era-defining collapse-one with ripple effects that still shape our society today. In 1929, the world watched in shock as the unstoppable Wall Street bull market went into a freefall, wiping out fortunes and igniting a depression that would reshape a generation. But behind the flashing ticker tapes and panicked traders, another drama unfolded-one of visionaries and fraudsters, titans and dreamers, euphoria and ruin. With unparalleled access to historical records and newly uncovered documents, New York Times bestselling author Andrew Ross Sorkin takes readers inside the chaos of the crash, behind the scenes of a raging battle between Wall Street and Washington and the larger-than-life characters whose ambition and naivete in an endless boom led to disaster. The dizzying highs and brutal lows of this era eerily mirror today's world-where markets soar, political tensions mount, and the fight over financial influence plays out once again. This is not just a story about money. 1929 is a tale of power, psychology, and the seductive illusion that "this time is different." It's about disregarded alarm bells, financiers who fell from grace, and skeptics who saw the crash coming-only to be dismissed until it was too late. Hailed as a landmark book, Too Big to Fail reimagined how financial crises are told. Now, with 1929, Sorkin delivers an immersive, electrifying account of the most pivotal market collapse of all time-with lessons that remain as urgent as ever. More than just a history, 1929 is a crucial blueprint for understanding the cycles of speculation, the forces that drive financial upheaval, and the warning signs we ignore at our peril"-- Provided by publisher.